Shift in precipitation regime promotes interspecific hybridization of introduced Coffea species - Gomez, Céline (Ecol Evol, 2016)
The frequency of plant species introductions has increased in a highly connected world, modifying species distribution patterns to include areas outside their natural ranges. These introductions provide the opportunity to gain new insight into the importance of flowering phenology as a component of adaptation to a new environment. Three Coffea species, C. arabica, C. canephora (Robusta), and C. liberica, native to intertropical Africa have been introduced to New Caledonia. On this archipelago, a secondary contact zone has been characterized where these species coexist, persist, and hybridize spontaneously. We investigated the impact of environmental changes undergone by each species following its introduction in New Caledonia on flowering phenology and overcoming reproductive barriers between sister species. We developed species distribution models and compared both environmental envelopes and climatic niches between native and introduced hybrid zones. Flowering phenology was monitored in a population in the hybrid zone along with temperature and precipitation sequences recorded at a nearby weather station. The extent and nature of hybridization events were characterized using chloroplast and nuclear microsatellite markers. The three Coffea species encountered weak environmental suitability compared to their native ranges when introduced to New Caledonia, especially C. arabica and C. canephora. The niche of the New Caledonia hybrid zone was significantly different from all three species' native niches based on identity tests (I Similarity and D Schoener's Similarity Indexes). This area appeared to exhibit intermediate conditions between the native conditions of the three species for temperature‐related variables and divergent conditions for precipitation‐related ones. Flowering pattern in these Coffea species was shown to have a strong genetic component that determined the time between the triggering rain and anthesis (flower opening), specific to each species. However, a precipitation regime different from those in Africa was directly involved in generating partial flowering overlap between species and thus in allowing hybridization and interspecific gene flow. Interspecific hybrids accounted for 4% of the mature individuals in the sympatric population and occurred between each pair of species with various level of introgression. Adaptation to new environmental conditions following introduction of Coffea species to New Caledonia has resulted in a secondary contact between three related species, which would not have happened in their native ranges, leading to hybridization and gene flow.